Acute respiratory distress syndrome after traumatic brain injury in Purwokerto-Indonesia - Munjiati Munjiati; Walin Walin; Herry Herry; Ferry Ferry (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Traumatic brain injury  was most source morbidity and mortality at patient by real trauma. Traumatic brain injury  case who dead before to the hospital was caused by shock, hypoxemia and hypercapnia. So needed basic of knowledge and ability to take care of patient of breath disease.Purpose: To explore the factors that influence respiratory distress on traumatic brain injury  at Prof. Dr. Margono Soekarjo hospital in Purwokerto, IndonesiaMethods: The kind of this research was correlation with using cross sectional approach. The population of this research was all patients with traumatic brain injury  in the emergency ward Prof. Dr. Margono Soekarjo hospital Purwokerto on November-Desember 2017. The sample take as 19 person. The analyzed used was Coefficient Contingency Test.Results: The result of this research shows that patient with traumatic brain injury had respiratory distress (57.9%) higher following by phlegm’s accumulation (52,6%) also had the decrease of consciousness (47,4%). There was real influence as statistic between phlegm’s accumulation and respiratory distress on traumatic brain injury (p=0.040). There was as statistically significant between the decrease of consciousness and respiratory distress on traumatic brain injury (p=0,009).Conclusion: It can be concluded that there was a statistically significant influence between decreased awareness of respiratory distress on traumatic brain injury (p=0.0009)